Urban governance, voice, and poverty in the developing world - Devas, Nick (Earthscan Publications, 2004)
Poverty and governance are both issues high on the agenda of international agencies and governments in the South. With urban areas accounting for a steadily growing share of the world's poor people an international team of researchers focused their attention on the hitherto little-studied relationship between urban governance and urban poverty. In their timely and in-depth examination of ten cities in Africa Asia and Latin America they demonstrate that in many countries the global trends towards decentralization and democratization offer new opportunities for the poor to have an influence on t.